Microsoft SQL Server 2000 unleashed - Rankins, Ray (Sams, 2003)
The book offers a variety of topics for system and database administrators to help them learn new features of the product and to solve problems they face on a daily basis. It shows them how to build upon their working knowledge of the product and take their experience and knowledge to a higher level. This title includes topics such as: SQL Server and XML; high availability; SQL Server architecture; performance and tuning; SQL Server and the Web; scalability issues; integration with BackOffice and other Microsoft® products; enterprise issues; replication; Data Transformation Services (DTS); security; and analysis services. This book is written by authors who offer the benefits of their experiences to help readers understand and solve problems such as performance issues, implementing critical backup and recovery strategies, and code efficient applications that work across a variety of platforms and systems. (Syndetic Solutions)